Therapeutic Effects and Mechanisms of Herbal Medicines for Treating Polycystic Ovary Syndrome: A Review - Kwon, Chan-Young; Cho, Ik-Hyun; Park, Kyoung Sun (Frontiers in Pharmacology, 2020)
Polycystic ovary syndrome (PCOS) is one of the most common disorders of reproductive endocrinology in reproductive-age women. In this study, we reviewed data on the effects and underlying mechanisms of herbal medicines used in the treatment of PCOS in laboratory studies. Articles published in English from their inception to June 30, 2018 were searched in Medline and EMBASE. We extracted data regarding the herbal intervention, target cell (or animal model), method of herbal extraction, route of administration, dosage and periods, and outcomes of the compounds isolated from herbs, individual herbal extracts, and herbal formula decoctions. We summarized the actions and the mechanisms underlying the beneficial effects of herbal medicines on PCOS. A total of 27 studies involving 22 herbal medicines reported their efficacy on PCOS. The herbal interventions in the 27 studies comprised four compounds isolated from herbs (six studies), nine individual herbal extracts (11 studies), and nine herbal formula decoctions (10 studies). Herbal medicine normalized female hormones, diminished male hormones, recovered the estrous cycle, ameliorated insulin resistance, and improved lipid metabolism in PCOS. The mechanisms underlying the beneficial effects of herbal medicines on PCOS are associated with anti-inflammation, anti-oxidative stress, inhibition of autophagy and/or apoptosis, and ovarian nerve growth factor reduction. Herbal medicines are thought to be promising resources in the development of effective therapeutic agents for PCOS. Further studies that include methodological quality assessment and quantitative synthesis of outcomes are recommended.